The Effect of Self-Control and Ease of Transactions on Impulsive Buying Tendencies - Alkusani Alkusani; Sukaris Sukaris; Heru Baskoro; Hendra Suwardana; Ahmad Qoni Dewantoro (Universitas Muhammadiyah Gresik, 2022)
The current era of digitalization makes people shop without using cash, this can then be related to the convenience factor that can encourage consumers to behave impulsively when shopping or without planning. At the same time consumers are also faced with a situation of ability to self control, for example when they see a new product discount and so on. Such a buying process without planning or suddenly without thinking about the benefits and functions of the item or often called impulsive buying. Another factor that can encourage is the ease of transaction. The sample was taken on students, the analysis tool used multiple linear regression analysis. The results of this study show that self-control and ease of transaction affect the tendency to buy impulsively. Therefore it is important that in the future research is carried out on all factors that stimulate impulsive tendencies both externally and internally to consumers.